2019
DOI: 10.1021/acs.bioconjchem.8b00855
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Subcellular Protein Delivery Using Cleavable Cyclic Cell-Penetrating Peptides

Abstract: The delivery of entire functional proteins into living cells is a long-sought goal in science. Cyclic cell-penetrating peptides (cCPPs) have proven themselves to be potent delivery vehicles to carry proteins upon conjugation into the cytosol of living cells with immediate bioavailability via a non-endosomal uptake pathway. With this strategy, we pursue the cytosolic delivery of mCherry, a medium-sized fluorescent protein. Afterward, we achieve subcellular delivery of mCherry to different intracellular loci by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 40 publications
2
58
0
2
Order By: Relevance
“…9 Among backbone modifications, cyclisation has been found to give remarkable results and is increasingly applied to CPPs. [10][11][12][13][14][15] In particular, cyclisation of Tat was found to improve cellular uptake by inducing maximal spacing between the CPP guanidinium groups, 11 in agreement with earlier observations made with peptoid analogues of CPPs. 16 Lipidation is another interesting modification, which can improve CPP interaction with the cell membrane leading to increased translocation efficiency.…”
supporting
confidence: 84%
“…9 Among backbone modifications, cyclisation has been found to give remarkable results and is increasingly applied to CPPs. [10][11][12][13][14][15] In particular, cyclisation of Tat was found to improve cellular uptake by inducing maximal spacing between the CPP guanidinium groups, 11 in agreement with earlier observations made with peptoid analogues of CPPs. 16 Lipidation is another interesting modification, which can improve CPP interaction with the cell membrane leading to increased translocation efficiency.…”
supporting
confidence: 84%
“…Therefore, we aimed for the cyclization of an R 10 peptide, which is, like other arginine-rich peptides, able to enhance the transduction of functional proteins into living cells when covalently attached to the protein cargo 48. We and others observed that the cellular transduction behavior is significantly improved for the cyclic version of cR 10 when compared to its linear counterpart 22,49,50. As an alternative to the previously applied cyclized R 10 -CPP 14 , we synthesized peptide 15 containing a cysteine and an azidohomoalanine residue to replace the former lactam bridge after our novel cyclization technique.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated the cleavage of peptides,bearing backbone Thz, using [PdCl(allyl)] 2 , [25,28] which is known to be compatible with reactions in live cells because of its reported low toxicity. [36] In addition, having one of the quenching pair on the CPP should allow loss of quenching upon Thzc leavage,r esulting in increased donor fluorescence. [33][34][35] Incorporation of backbone Thz, however,remains out of scope for genetic manipulation, making chemical protein synthesis essential for this task.…”
Section: Resultsmentioning
confidence: 99%